The Effect of Morphological Characteristic of Coarse Aggregates Measured with Fractal Dimension on Asphalt Mixture’s High-Temperature Performance - Hainian Wang; Yin Bu; Yanzhe Wang; Xu Yang; Zhanping You (Advances in Materials Science and Engineering)
The morphological properties of coarse aggregates, such as shape, angularity, and surface texture, have a great influence on the mechanical performance of asphalt mixtures. This study aims to investigate the effect of coarse aggregate morphological properties on the high-temperature performance of asphalt mixtures. A modified Los Angeles (LA) abrasion test was employed to produce aggregates with various morphological properties by applying abrasion cycles of 0, 200, 400, 600, 800, 1000, and 1200 on crushed angular aggregates. Based on a laboratory-developed Morphology Analysis System for Coarse Aggregates (MASCA), the morphological properties of the coarse aggregate particles were quantified using the index of fractal dimension. The high-temperature performances of the dense-graded asphalt mixture (AC-16), gap-graded stone asphalt mixture (SAC-16), and stone mastic asphalt (SMA-16) mixtures containing aggregates with different fractal dimensions were evaluated through the dynamic stability (DS) test and the penetration shear test in laboratory. Good linear correlations between the fractal dimension and high-temperature indexes were obtained for all three types of mixtures. Moreover, the results also indicated that higher coarse aggregate angularity leads to stronger high-temperature shear resistance of asphalt mixtures.